The Needs Assessment of Training Course to Enhance the Lesson Study Process for Lecturers of Souphanouvong University, Lao PDR - Vathanavong, Thongthiane; Tungkasamit, Angkana; Thinwiangthong3, Sampan (Acitya: Journal of Teaching and Education, 2024)
The purposes of this research were: 1) to study the state of the problems of teaching and learning for lecturers; 2) to undertake a needs assessment for training to promote the lesson study process for lecturers; and 3) to compare the state of the problems and the needs assessment for training to promote the lesson study process. The study sample comprised 54 administrators; 167 lecturers and 327 students from six faculties of Souphanouvong University who were selected by stratified random sampling. Mixed methods were used as the research methodology; an Embedded Design was conducted by studying quantitative methods and supplementing with qualitative methods. Research Instruments used to collect the data were a questionnaire and structured interviews. Statistics used included percentage, mean, standard deviation (S.D.) and Priority Needs Index Modified (PNIModified). T-test and One Way MANOVA was applied. The research results were as follows: 1) The state of the problems of teaching and learning for lecturers, including the overall average, was medium; 2) A needs assessment of training to promote the lesson study process by all groups of the sample was an essential requirement for all items, with the overall average of 0.35; and 3) The state of the problems and needs assessment of training to promote the lesson study process, as classified by samples group, showed no difference in significance except for administrators and lecturers, which was different for the state of the problems at the .05 level of statistical significance.